2022
DOI: 10.1111/caje.12582
|View full text |Cite
|
Sign up to set email alerts
|

Education and income gradients in longevity: The role of policy

Abstract: Education and income are strong predictors of health and longevity. In the last 20 years, many efforts have been made to understand if these relationships are causal and what the possible role of policy should be as a result. The evidence from various studies is ambiguous: the effects of education and income policies on health are heterogeneous and vary over time and across places and populations. I discuss explanations for these disparate results and suggest directions for future research.Résumé. Gradients d'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 176 publications
0
4
0
Order By: Relevance
“…Existing research has found somewhat mixed effects of CSLs using IV, 7 potentially due to limited power or because of underlying heterogeneity in the impacts of increased schooling. 26 Our research tried to address prior challenges by using a 1% population sample, all death certificate data, and ITT estimates. By combining ACS population data with the national vital statistics data, we simulated a national cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research has found somewhat mixed effects of CSLs using IV, 7 potentially due to limited power or because of underlying heterogeneity in the impacts of increased schooling. 26 Our research tried to address prior challenges by using a 1% population sample, all death certificate data, and ITT estimates. By combining ACS population data with the national vital statistics data, we simulated a national cohort.…”
Section: Discussionmentioning
confidence: 99%
“…They show that they show that a one-unit decrease in average blood lead level is associated with about 8 percent in the probability of being below proficient in reading. The skill developments specifically through cognitive skills and educational attainments may affect old-age longevity through several channels, such as increases in income, occupational choice, social relations, peer selection, and labor market outcomes (Buckles et al, 2016;Cutler et al, 2015;Fletcher, 2012Fletcher, , 2015Fletcher & Frisvold, 2014Fletcher & Marksteiner, 2017;Lleras-Muney, 2022;Lleras-Muney et al, 2020;Lleras-Muney, 2005;Meghir et al, 2018;Savelyev, 2020;Savelyev et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using a large dataset for the US, [ 1 ] confirmed that income inequalities are associated with longevity inequalities, but the literature is still non conclusive about causal effects [ 29 ]. Within these studies, geographical differences in longevity are often mentioned and more and more analyzed.…”
Section: Introductionmentioning
confidence: 99%